2021
DOI: 10.3390/su13126600
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Analysis between Economic Growth and Air Pollution in Key Regions of Air Pollution Control in China

Abstract: The Chinese government has implemented a number of environmental policies to promote the continuous improvement of air quality while considering economic development. Scientific assessment of the impact of environmental policies on the relationship between air pollution and economic growth can provide a scientific basis for promoting the coordinated development of these two factors. This paper uses the Tapio decoupling theory to analyze the relationship between regional economic growth and air pollution in key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In 2018, China promulgated an updated version of APPCAP, that is, the Three Year Action Plan to Beat Air Pollution, which aims to further strengthen the joint prevention and control of air pollution [ 16 ]. Thus, to eliminate the effect of the Three Year Action Plan to Beat Air Pollution, the sample of this study included 285 prefecture-level and above cities in China from 2007 to 2017, excluding the cities dismantled and established during the research period, and the cities with severe data loss and inaccessibility.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, China promulgated an updated version of APPCAP, that is, the Three Year Action Plan to Beat Air Pollution, which aims to further strengthen the joint prevention and control of air pollution [ 16 ]. Thus, to eliminate the effect of the Three Year Action Plan to Beat Air Pollution, the sample of this study included 285 prefecture-level and above cities in China from 2007 to 2017, excluding the cities dismantled and established during the research period, and the cities with severe data loss and inaccessibility.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the goals of air pollutant concentration control were initially proposed in the 12th Five-Year Plan on Air Pollution Prevention and Control in Key Regions issued on 29 October 2012, and strengthened in the 12th Five-Year Plan on Air Pollution Prevention and Control Action Plan issued on 10 September 2013 [ 15 , 16 ]. As the first comprehensive plan for air pollution prevention and control, APPCAP comprises a series of detailed contents, including ten key actions and 35 concrete measures, detailed assessment plans and clear accountability models for local governments, and substantial measures and supporting policies [ 5 ].…”
Section: Policy Background Of the Appcapmentioning
confidence: 99%
See 1 more Smart Citation
“…This research revealed a strong correlation between the pollution of the air and the growth of the economy. The study indicated that interventions from relevant authorities to help improve the situation by lowering pollution and maintaining economic growth were essential [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional economic growth model has caused resource exhaustion and is difficult for sustainable development [3].Frequent air pollution has a significant impact on human health [4,5]. It is showed that air pollution has serious impact on the general public and has become a major bottleneck for China's sustainable development [6]. In recent years, China's government attaches great importance on increasing the environmental investment and promoting the upgrading of the industrial structure.…”
Section: Introductionmentioning
confidence: 99%